Komunikasi Persuasif Apoteker Sumber Sehat Bintara melalui Live Streaming E-Commerce Shopee - Rachmawati, Diva Alya; Imaddudin, Imaddudin (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2024)
The live streaming feature is used by pharmacists to introduce products sold in pharmacies online to help consumers meet the information and needs of pharmacists in providing counseling and marketing drugs that can be accessed freely through digital platforms such as Shopee. Introduce him to persuasive communication which consists of five techniques. This research aims to determine the implementation of pharmacists' persuasive communication via live streaming on Shopee e-commerce. This type of research is qualitative with descriptive methods. Data collection techniques include observation, interviews and documentation, then the results are reduced for analysis and conclusions are drawn. The research results show that persuasive communication is carried out consciously or unconsciously using five persuasive communication techniques in live streaming. Another fact is that techniques that live streaming viewers are not yet aware of are setting and red-herring techniques. Meanwhile, the technique that gets a positive response from the audience is the reward technique which provides persuasive power to the audience.